The prescription of benzodiazepines in Brazil: a literature review - Fiorelli, Katiana (2017)
Benzodiazepines are prescription restricted psychotropic drugs, subject to special control according to Decree nº 344 of May 12, 1998. They are used as hypnotics and sedatives, being widely used in clinical practice. Prolonged use of these drugs can cause dependence, and therefore it is necessary to identify their prescription profile. This study aims to review the literature on studies that described the use of benzodiazepines in Brazil. For such, a direct search was conducted in databases, such as LILACS, Pubmed and SciELO, with the descriptors, in Portuguese and English, “prescrição” (prescription), “benzodiazepínicos” (benzodiazepines) and “Brasil” (Brazil). After applying the criteria for inclusion and exclusion, 12 articles remained, which were analyzed in this work. The analysis of these data has shown that, in Brazil, benzodiazepines are used especially by women with a tendency to increased use with advancing age. On this wat, we might conclude that Brazil’s needs to improve his politics to promote rational use of Benzodiazepines.